Breast conservative surgery and local recurrence. (1st November 2015) - Rezai, Mahdi; Kraemer, Stefan; Kimmig, Rainer; Kern, Peter
Abstract: Introduction: Breast conservation is a legacy of Umberto Veronesi who laid the groundwork for the preservation of the body image of women affected by breast cancer (BC) with the Milan I study in the late 70ies of the last millennium. Breast conservative surgery (BCS) has two aspects: oncological safety of tumour resection with free margins and aesthetic preservation of the breast. Determinants of local control used to be T-size, nodal status and receptor status until biologically driven concepts defined risk of recurrence on the basis of molecular portraits. We explored whether these concepts of intrinsic subtypes prove at a large scale in the context of BCS and which surgical techniques procure best oncological and aesthetic outcomes, avoiding re-excision and necessity of conversion to mastectomy. Patients and methods: We analyzed 1035 BCS patients with primary unilateral breast cancer (2004–2009) with regards to the local recurrence as a function of tumour location, surgical technique, resection volume, T-size, nodal status, grading, histopathological and intrinsic subtype and margins. Results: Five surgical techniques were applied to 944 eligible patients at a median follow-up of 5.2 years with the following frequency: Glandular rotation mammoplasty (63.8%), tumour-adapted rotation mammoplasty (20.9%), dermoglandular rotation mammoplasty (6.7%), 4.4% (lateral thoracic wall advancement), 0.7% latissimus dorsi flap (0.7%) and others (13.5%). Tumour-free margins were achieved in 88.6% of all patients at first surgery. Recurrence was independent of the surgical technique used, resection volume, T-size (in a T1/T2-cohort), nodal status (in low N-stages: NO/N1) and histopathology (inv.-ductal vs. lobular), however non-invasive subtype (DCIS), high grading (G3 vs. G1), non-luminal Her2 positive BC and triple-negative breast cancer (TNBC) were significantly associated with local recurrence. Conclusions: Five defined oncoplastic principles presented in our nomogramme (targeted breast surgery) allow the reconstruction of major segmental resection defects during breast-conserving therapy with high clinical applicability and result in favorable oncological and aesthetic outcome. Recurrence was not a function of traditional prognostic factors like T-size or nodal status (in a T1/T2, N0/N1 cohort), but of grading, intrinsic subtypes and non-invasive breast cancer components. Lobular histology, multi-centricity and DCIS were predictive for breast preservation failure and conversion to mastectomy.